Pengembangan Wakaf Produktif Berbasis Pesantren Ditinjau dengan Analisis SWOT - Wiwik Erik Setiawan; Yudianto Achmad; MH Ainulyaqin; Achmad, LI; S Edy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to determine the development of Islamic boarding school-based productive waqf, reviewed using a SWOT analysis. This research uses a qualitative approach, with data collection methods in the form of interviews with informants, direct observation at the Albinaa Islamic boarding school, and study of related literature. The research results showed that in terms of strength, the development of Albinaa's productive waqf has been good considering that at the age of three years Bina Enterprise already has various business units such as: Al Binaa Shop, Bina Resto, Bina Tour, Binaa Food Online,